Effects of Transcranial Static Magnetic Stimulation on Motor Cortex Evaluated by Different TMS Waveforms and Current Directions. (10th August 2019) - Davila-Pérez, Paula; Pascual-Leone, Alvaro; Cudeiro, Javier
Abstract: Transcranial static magnetic stimulation (tSMS) modulates cortical excitability probably by interacting with the GABA-glutamate intracortical balance. Different transcranial magnetic stimulation (TMS) waveforms probe distinct GABA-mediated cortical inhibition networks. The goal of the present work is to further characterize tSMS-induced changes in motor cortex reactivity and inhibition–excitation (I/E) balance. We hypothesized that tSMS affects particular cortical networks and thus, the effects of tSMS would be different depending on the TMS waveform used to assess its results. 23 healthy young adults completed two sessions of real or sham tSMS. The order of the sessions was randomized across participants. Motor evoked potentials (MEPs), cortical silent period (CSP), short- and long-interval intracortical inhibition (SICI and LICI), and intracortical facilitation (ICF) were assessed with TMS monophasic posterior–anterior (monoPA ; n = 9), monophasic anterior–posterior (monoAP ; n = 7), or biphasic (biAP-PA ; n = 7) pulses. Repeated measures analyses of variance and appropriate pairwise comparisons were performed for each TMS measure. After 15 min of real tSMS, the MEP amplitudes decreased compared to sham and baseline, SICI and LICI showed greater inhibition, and a tendency towards longer CSPs and less facilitation was found. These results were only observed with monoPA TMS. MEP amplitude increased compared to sham with monoAP TMS, with no clear changes in general intracortical I/E balance. Biphasic TMS was not able to capture any effects of tSMS. The results show that the effects of tSMS on cortical excitability and inhibition involve specific interneuron circuits that are selectively activated by monoPA TMS. Highlights: tSMS-induced inhibition was tested with different TMS waveforms. Inhibition after single- and paired-pulse TMS was only observed with monophasic PA pulses. Monophasic AP revealed larger motor responses after tSMS with no change in intracortical I/E balance. Biphasic TMS did not capture any inhibitory cortical changes due to tSMS. tSMS induces inhibition via specific GABA-mediated cortical networks.